2007
DOI: 10.1016/j.socscimed.2007.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Understanding social disparities in hypertension prevalence, awareness, treatment, and control: The role of neighborhood context

Abstract: The spatial segregation of the U.S. population by socioeconomic position and especially raceethnicity suggests that the social contexts or "neighborhoods" in which people live may substantially contribute to social disparities in hypertension. The Chicago Community Adult Health Study did face-to-face interviews, including direct measurement of blood pressure, with a representative probability sample of adults in Chicago. These data were used to estimate socioeconomic and racialethnic disparities in the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
254
4
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(274 citation statements)
references
References 25 publications
9
254
4
7
Order By: Relevance
“…Poor socioeconomic status has been found to be related to the lack of adherence in antihypertensive drugs in previous studies. 4,9,27,28 We did not find a clear relationship between income and risk of discontinuation. This suggests that the effect of income disparities in keeping with antihypertensive treatment might be mitigated from the universal coverage for drug treatment for hypertension supplied from the Italian NHS.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Poor socioeconomic status has been found to be related to the lack of adherence in antihypertensive drugs in previous studies. 4,9,27,28 We did not find a clear relationship between income and risk of discontinuation. This suggests that the effect of income disparities in keeping with antihypertensive treatment might be mitigated from the universal coverage for drug treatment for hypertension supplied from the Italian NHS.…”
Section: Discussioncontrasting
confidence: 67%
“…2,3 Socioeconomic factors, such as income, education and ethnicity, have been extensively investigated as possibly associated with the rate of treatment and control of hypertension. [4][5][6][7][8][9] However, data on this issue mainly reflect private, or mixed publicprivate, health care systems. Despite the fact that the Italian National Health Service (NHS) provides universal coverage for health care, including drug treatment for hypertension, socioeconomic disparities in the occurrence of coronary heart disease still persist.…”
Section: Introductionmentioning
confidence: 99%
“…15,18,20 Third, our screening survey did not include several important variables, including educational attainment, income, routine sources of health care, and knowledge regarding hypertension, which other studies have shown to be predictors of awareness, treatment, and control. 18,29,32,35,36 Finally, white coat hypertension could modify the prevalence of hypertension in the unaware group, since hypertension was defined using 1 day of BP readings. 2 Following recommendations, we took repeated measurements that were at least 3 min apart and used the last two out of three measurements to reduce the chance of wrongly detecting hypertension.…”
Section: Controlmentioning
confidence: 99%
“…[13][14][15][16] In spite of the potential ramifications that gentrification carries onto health, no study to date has sought to untangle the complex relationships between gentrification and health using this method. Through hierarchical modeling, we answer the question of how an individual's race/ethnicity moderates the effects of neighborhood gentrification on their health.…”
Section: Introductionmentioning
confidence: 99%